Substrate for liquid filter
By using polyolefin microporous membrane as the substrate for liquid filters, the problem of filtration time deviation in small-pore liquid filters is solved, and the effect of uniform filtration and extended life is achieved.
Patent Information
- Application Number
- CN202380056154.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-27
- Publication Date
- 2025-03-11
AI Technical Summary
In the base material for liquid filters with small pore diameters, deviations in the width direction of the filtration time are prone to occur, resulting in uneven filtration and affecting performance and life.
A polyolefin microporous membrane is used as the substrate for liquid filters, with an average pore diameter of 1 nm to 50 nm, an average water flow rate of 0.003L/min/ft2/psi to 0.180L/min/ft2/psi, and a coefficient of variation of the water flow rate is controlled below 0.100.
It effectively suppresses the deviation of filtration time, ensures the overall uniform filtration of the liquid filter, and extends the performance and life of the filter.
Smart Images

Figure BDA0005256172250000441 
Figure BDA0005256172250000451
Abstract
Description
Technical Field
[0001] The present disclosure relates to substrates for liquid filters. Background Art
[0002] In recent years, electronic devices have been increasingly miniaturized and highly functional. In particular, digital devices and mobile terminals, represented by personal computers and smartphones, are making rapid progress. It is well known that technological innovation in the semiconductor industry has played a major role in promoting and supporting this progress. In recent years, the semiconductor industry has shown a trend of developing competition in the field of less than 10nm in terms of wiring pattern size, and companies are eager to establish the most advanced manufacturing pipelines.
[0003] The photolithography process is a process for forming patterns in the manufacture of semiconductor components. With the miniaturization of patterns in recent years, not only the properties of the chemical solution used in the photolithography process itself are required, but also a very high level of technology is required for the treatment of the chemical solution applied to the wafer.
[0004] The chemical solution that has been prepared through complex processes is filtered with a fine liquid filter just before being applied to the wafer, thereby removing tiny foreign matter and gel-like foreign matter from the chemical solution that have a significant impact on pattern formation and yield. In the formation of the most advanced wiring pattern with a pattern size of less than 10nm, as the wiring pattern size is miniaturized to 10nm to several nm, in order to capture tiny foreign matter of less than 5nm in the chemical solution, a liquid filter with a finer pore size and good permeability is required. Therefore, filter manufacturers are actively developing liquid filters for advanced semiconductors.
[0005] As a liquid filter substrate that can be suitably used for a fine liquid filter, a liquid filter substrate including a polyolefin microporous membrane having a small pore size is known (for example, see Patent Documents 1 to 7).
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-218563
[0007] Patent Document 2: Japanese Patent Application Publication No. 2014-217800
[0008] Patent Document 3: Japanese Patent No. 5684951
[0009] Patent Document 4: Japanese Patent No. 5684952
[0010] Patent Document 5: Japanese Patent No. 5684953
[0011] Patent Document 6: Japanese Patent Application Publication No. 2018-167198
[0012] Patent Document 7: Japanese Patent No. 6805371 Summary of the invention
[0013] Problems to be solved by the invention
[0014] In a liquid filter substrate having a micropore size of 50 nm or less, the problem of deviation of the filtration time in the width direction of the liquid filter substrate is easy to occur. In the case of uneven filtration time of the liquid filter, for example, low pressure in the center of the filter and high pressure at the ends of the filter, the pressure applied to the filter in the width direction is easy to become uneven, and the liquid cannot be filtered uniformly in the entire filter. As a result, there is a concern that the filter performance and filtration life will be reduced, or the manufacturing yield of the semiconductor will be reduced.
[0015] The present disclosure has been made in view of the above-mentioned conventional problems, and an object of the present disclosure is to provide a substrate for a liquid filter which can suppress the variation in filtration time even when the pore diameter is small.
[0016] Means for solving problems
[0017] The specific means for achieving the above-mentioned objects are as follows.
[0018] <1> A liquid filter substrate, comprising a polyolefin microporous membrane.
[0019] The average pore size of the polyolefin microporous membrane is 1 nm to 50 nm.
[0020] The average water flow rate of the polyolefin microporous membrane is 0.003 L / min / ft 2 / psi~0.180L / min / ft 2 / psi,
[0021] The coefficient of variation of the water flow rate of the polyolefin microporous membrane is 0.100 or less.
[0022] <2> like <1> In the liquid filter substrate, the coefficient of variation of the pore size of the polyolefin microporous membrane is 0.100 or less.
[0023] <3> like <1> or <2> In the liquid filter substrate, the coefficient of variation of the film thickness of the polyolefin microporous film is 0.100 or less.
[0024] <4> like <1> ~ <3> The liquid filter substrate according to any one of the preceding claims, wherein the coefficient of variation of the porosity of the polyolefin microporous membrane is 0.100 or less.
[0025] <5> like <1> ~ <4> The liquid filter substrate according to any one of the preceding claims, wherein the polyolefin microporous membrane has an average thickness of 3 μm to 20 μm.
[0026] <6> like <1> ~ <5> The liquid filter substrate according to any one of the preceding claims, wherein the average porosity of the polyolefin microporous membrane is 35% to 60%.
[0027] Effects of the Invention
[0028] According to the present disclosure, it is possible to provide a substrate for a liquid filter which can suppress variations in filtration time even when the pore diameter is small. DETAILED DESCRIPTION
[0029] Hereinafter, the embodiments of the present disclosure are described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, except for the cases specifically described, the constituent elements (including element steps, etc.) are not essential. Regarding numerical values and their ranges, the present disclosure is also not limited.
[0030] In the present disclosure, the term "process" includes not only a process independent of other processes, but also a process that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved.
[0031] In the present disclosure, in a numerical range expressed using "to", the numerical values described before and after "to" are included as the minimum value and the maximum value, respectively.
[0032] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.
[0033] In the present disclosure, each component may include multiple corresponding substances. When multiple corresponding substances exist in the composition, unless otherwise specified, the content or content of each component refers to the total content or content of the multiple substances present in the composition.
[0034] In the present disclosure, the term "layer" or "film" includes not only the case where the layer or film is formed on the entire region when observing the region where the layer or film exists, but also includes the case where the layer or film is formed on only a part of the region.
[0035] In the present disclosure, regarding the polyolefin microporous membrane, the "length direction" refers to the long dimension direction of the polyolefin microporous membrane manufactured into a long strip, and the "width direction" refers to the direction orthogonal to the length direction of the polyolefin microporous membrane. Hereinafter, the "width direction" is also referred to as "TD" and the "length direction" is referred to as "MD".
[0036] In addition, the "width direction" in the liquid filter substrate refers to the same direction as the direction orthogonal to the longitudinal direction of the polyolefin microporous membrane.
[0037] [Liquid filter substrate]
[0038] The liquid filter substrate of the present disclosure is a liquid filter substrate comprising a polyolefin microporous membrane, wherein the average pore size of the polyolefin microporous membrane is 1 nm to 50 nm, and the average water flow rate of the polyolefin microporous membrane is 0.003 L / min / ft 2 / psi~0.180L / min / ft 2 / psi, and the coefficient of variation of the water flow rate of the polyolefin microporous membrane is 0.100 or less.
[0039] According to the liquid filter substrate of the present disclosure, even with a small pore size, the variation in filtration time can be suppressed. The reason for this is not clear, but it is presumed as follows.
[0040] In the liquid filter substrate of the present disclosure, the average water flow rate of the polyolefin microporous membrane is set to 0.003 L / min / ft 2 / psi~0.180L / min / ft 2 / psi, so it is easy to obtain not only sufficient water permeability as a liquid filter, but also stability of liquid delivery through the filter over a long period of time. In addition, in the liquid filter substrate of the present disclosure, the average pore size of the polyolefin microporous membrane is set to 1nm to 50nm, so sufficient liquid permeability can be obtained, and, for example, microparticles of about 10nm or less can be captured at a very high level. Based on the above, it can be inferred that the liquid filter substrate of the present disclosure can effectively function as a liquid filter for advanced semiconductors.
[0041] On the other hand, when the average pore size of the polyolefin microporous membrane is a small pore size of 50 nm or less, there is a tendency that the filtration time tends to vary in the width direction of the liquid filter substrate. However, it is speculated that in the present disclosure, the coefficient of variation of the water flow rate of the polyolefin microporous membrane is set to 0.100 or less, so that the pressure is not easy to become uneven in the width direction of the filter, and the variation of the filtration time can be suppressed.
[0042] As described above, the liquid filter substrate of the present disclosure can easily filter the liquid uniformly in the entire filter, and as a result, there is a tendency to easily suppress the degradation of the filter performance and the reduction of the filter life.
[0043] (Polyolefin Microporous Membrane)
[0044] The liquid filter substrate of the present disclosure includes a polyolefin microporous membrane. The liquid filter substrate of the present disclosure may be a substrate formed only of a polyolefin microporous membrane, or may be a substrate formed by laminating a polyolefin microporous membrane with other layers (e.g., a coating layer or a porous substrate). In addition, the polyolefin microporous membrane may also be a laminated membrane having a structure formed by laminating a plurality of polyolefin porous layers.
[0045] The polyolefin microporous membrane is a microporous membrane composed of polyolefin. Here, the microporous membrane refers to a membrane having a large number of micropores inside and having a structure in which these micropores are connected, and gas or liquid can pass from one surface to the other surface.
[0046] The polyolefin microporous membrane preferably contains 90 parts by mass or more of polyolefin based on 100 parts by mass of the polyolefin microporous membrane, and the remainder may contain additives such as organic fillers, inorganic fillers, and surfactants within a range that does not affect the effects of the present disclosure.
[0047] (Aperture)
[0048] In the present disclosure, the average value of the pore size of the polyolefin microporous membrane is 1nm to 50nm. The average value of the pore size is 1nm to 50nm, which indicates a small pore size. When the average value of the pore size of the polyolefin microporous membrane is 1nm or more, sufficient liquid permeability as a liquid filter can be obtained. From this point of view, the average value of the pore size is preferably 10nm or more, more preferably 11nm or more, and further preferably 13nm or more. On the other hand, when the average value of the pore size of the polyolefin microporous membrane is 50nm or less, it is possible to capture very small particles of, for example, about 10nm. From this point of view, the average value of the pore size is preferably 40nm or less, more preferably 30nm or less, further preferably 25nm or less, and particularly preferably 20nm or less.
[0049] In the present disclosure, from the viewpoint of further suppressing the deviation of the filtration time, the coefficient of variation of the pore size of the polyolefin microporous membrane is preferably 0.100 or less, more preferably 0.095 or less, further preferably 0.093 or less, and particularly preferably 0.085 or less. The coefficient of variation of the pore size may be 0.0015 or more, preferably 0.020 or more, and more preferably 0.024 or more. The coefficient of variation of the pore size is preferably 0.0015 to 0.100.
[0050] In the present disclosure, the value of the pore size of the polyolefin microporous membrane and its average value and coefficient of variation are values obtained by the method described in the Example column.
[0051] (Water flow)
[0052] In this disclosure, the average water flow rate of the polyolefin microporous membrane is 0.003 L / min / ft 2 / psi~0.180L / min / ft 2 / psi. The average water flow rate of the polyolefin microporous membrane is 0.003L / min / ft 2 / psi or more, it is easy to obtain sufficient water permeability as a liquid filter, and it is easy to obtain stability of liquid delivery through the filter over a long period of time (for example, stability of the power load for maintaining a certain liquid delivery amount, stability of the liquid delivery amount under a certain liquid delivery pressure (a certain power load)), so it is preferred. From this point of view, the average water flow rate of the polyolefin microporous membrane is preferably 0.004L / min / ft 2 / psi or more, more preferably 0.005L / min / ft 2 / psi or more. On the other hand, the average water flow rate of the polyolefin microporous membrane is 0.180L / min / ft 2 / psi or less, for example, it is easy to capture fine particles of about 10nm or less, so it is preferred. From this point of view, the average water flow rate of the polyolefin microporous membrane is preferably 0.150L / min / ft 2 / psi or less, more preferably 0.100L / min / ft 2 / psi or less.
[0053] In the present disclosure, from the viewpoint of further suppressing the deviation of the filtration time, the coefficient of variation of the water flow rate of the polyolefin microporous membrane is 0.100 or less, preferably 0.095 or less, more preferably 0.090 or less, and further preferably 0.080 or less. The coefficient of variation of the water flow rate may be 0.010 or more, preferably 0.015 or more, and more preferably 0.018 or more. The coefficient of variation of the water flow rate is preferably 0.010 to 0.100.
[0054] In the present disclosure, the value of the water flow rate of the polyolefin microporous membrane and its average value and coefficient of variation are values obtained by the method described in the Example column.
[0055] (film thickness)
[0056] In the present disclosure, the average value of the film thickness of the polyolefin microporous membrane is preferably 3 μm to 20 μm. When the average value of the film thickness of the polyolefin microporous membrane is 3 μm or more, it is easy to obtain sufficient mechanical strength, easy to obtain operability when processing the polyolefin microporous membrane, and durability when the filter cartridge is used for a long time, so it is preferred. From this point of view, the average value of the film thickness of the polyolefin microporous membrane is more preferably 4 μm or more, further preferably 5 μm or more, and particularly preferably 6 μm or more. On the other hand, when the average value of the film thickness is less than 20 μm, not only the thickness variation in the width direction of the polyolefin microporous membrane is reduced when the polyolefin microporous membrane is a single membrane, but also sufficient liquid permeability can be obtained, and a larger filtration area can be easily obtained in a filter cartridge of a specified size, and the flow design and structural design of the filter when processing the polyolefin microporous membrane become easy, so it is preferred. From this point of view, the average value of the film thickness of the polyolefin microporous membrane is more preferably 18 μm or less, more preferably 16 μm or less, and particularly preferably 14 μm or less.
[0057] For example, in the case where the filter cartridge is accommodated in a housing of the same size, the thinner the thickness of the filter material (the structural material as a whole including the filter substrate), the more the filter material area can be increased, so that the design of high flow and low filtration pressure preferred as a liquid filter can be realized. That is, as a liquid filter, it can be designed in the following manner: when you want to maintain the same flow, the filtration pressure is reduced, and when you want to maintain the same filtration pressure, the flow rate is increased. In particular, by reducing the filtration pressure, the following effects can be expected: the probability of leakage of the foreign matter that has been temporarily captured due to continuous exposure to the filtration pressure inside the filter material and being squeezed out of the filter material together with the filtrate over time is significantly reduced. In addition, by reducing the filtration pressure, the following effects can also be expected: the probability of the gas dissolved in the liquid to be filtered appearing in the form of tiny bubbles due to the pressure difference before and after filtration (pressure reduction after filtration) is significantly reduced. In addition, the following effects can also be expected: the filtration efficiency of the filter object such as chemical liquid is improved; and the quality of the filter object such as chemical liquid is maintained at a high level for a long time.
[0058] On the other hand, the thinner the filter material is, the lower its strength and durability will be. However, in filter design, for example, the durability and flow rate can be adjusted while strengthening the filter material by compounding it with a high-strength support of a coarse screen (for example, by stacking and sandwiching).
[0059] In the present disclosure, from the viewpoint of further suppressing the deviation of the filtration time, the coefficient of variation of the film thickness of the polyolefin microporous membrane is preferably 0.100 or less, more preferably 0.095 or less, further preferably 0.090 or less, and particularly preferably 0.065 or less. The coefficient of variation of the film thickness may be 0.0015 or more, preferably 0.018 or more, and more preferably 0.020 or more. The coefficient of variation of the film thickness is preferably 0.0015 to 0.100.
[0060] In the present disclosure, the value of the film thickness of the polyolefin microporous film and its average value and coefficient of variation are values obtained by the method described in the Example column.
[0061] (Porosity)
[0062] In the present disclosure, the average porosity of the polyolefin microporous membrane is preferably 35% to 60%. When the average porosity of the polyolefin microporous membrane is 35% or more, the liquid permeability becomes good. From this point of view, it is more preferably 36% or more, further preferably 38% or more, and particularly preferably 40% or more. On the other hand, when the average porosity is 60% or less, it is preferred from the perspective of improving the mechanical strength of the polyolefin microporous membrane and improving the operability. From this point of view, the average porosity of the polyolefin microporous membrane is more preferably 59% or less, further preferably 58% or less, and particularly preferably 55% or less.
[0063] In the present disclosure, from the viewpoint of further suppressing the deviation of the filtration time, the coefficient of variation of the porosity of the polyolefin microporous membrane is preferably 0.100 or less, more preferably 0.095 or less, further preferably 0.090 or less, and particularly preferably 0.075 or less. The coefficient of variation of the porosity may be 0.020 or more, preferably 0.025 or more, and more preferably 0.026 or more. The coefficient of variation of the porosity is preferably 0.020 to 0.100.
[0064] In the present disclosure, the porosity value of the polyolefin microporous membrane and its average value and coefficient of variation are values obtained by the method described in the Example column.
[0065] (Calcium content)
[0066] In the present disclosure, the calcium content in the polyolefin microporous membrane is preferably less than 2000ppb. If the calcium content is less than 2000ppb, not only can the cleaning time when manufacturing the filter cartridge be significantly shortened, but also the solvents such as water used for cleaning can be greatly reduced. From such a viewpoint, the calcium content of the polyolefin microporous membrane is more preferably less than 1500ppb, further preferably less than 1300ppb, particularly preferably less than 1000ppb, and extremely preferably less than 800ppb. On the other hand, from the viewpoint of the manufacturing efficiency of the filter cartridge, the calcium content is preferably as little as possible. However, in reality, there are cases where trace amounts of calcium are contained in the manufacturing raw materials or trace amounts of calcium are mixed into the manufacturing process of the polyolefin microporous membrane, so it is difficult to reduce the calcium content. The calcium content of the polyolefin microporous membrane can be more than 0ppb, can be more than 1ppb, can be more than 10ppb, and can be 50ppb. If the calcium content is less than 2000ppb, the manufacturing efficiency of the filter cartridge can be greatly improved.
[0067] In addition, in the present disclosure, a polyolefin microporous membrane with micropores having an average pore size of 1nm to 50nm is applied. Such a polyolefin microporous membrane with micropores has a tendency that the specific surface area becomes significantly larger and the dissolved metal ions and the like also increase. However, if the calcium content is less than 2000ppb, even such a polyolefin microporous membrane with micropores can greatly improve the manufacturing efficiency of the filter cartridge. In addition, if the calcium content of the polyolefin microporous membrane is more than 1ppb, the chloride ions from the polymerization catalyst that may remain in the polyolefin in trace amounts can be fully neutralized, and the possibility of corrosion of stainless steel and other piping in the manufacturing equipment of the polyolefin microporous membrane is eliminated. From such a viewpoint, the calcium content of the polyolefin microporous membrane is preferably more than 10ppb, more preferably more than 50ppb.
[0068] It should be noted that in the present disclosure, there is no particular limitation on the method for adjusting the calcium content of the polyolefin microporous membrane to 2000 ppb or less, and for example, the following methods can be mentioned: using a polyolefin having a calcium content of 0 ppb or more and 1000 ppb or less as a polyolefin raw material constituting the polyolefin microporous membrane; washing the polyolefin microporous membrane for a long time with an acid or the like after manufacturing the polyolefin microporous membrane; etc. From the viewpoint of being able to sufficiently reduce the calcium content even inside the polyolefin microporous membrane, it is preferred to use a polyolefin raw material having a low calcium content.
[0069] In the present disclosure, the calcium content in the polyolefin microporous membrane refers to a value determined by the method described in the Example column.
[0070] In addition, there is no particular limitation on the method for controlling the porous structure of the polyolefin microporous membrane. For example, the composition of the polyolefin resin, the concentration of the polyolefin resin in the raw material, the mixing ratio of the solvents when the raw material is mixed with multiple solvents, the heating temperature for squeezing out the solvent inside the extruded sheet, the extrusion pressure, the heating time, the stretching ratio, the heat treatment (heat setting) temperature after stretching, the immersion time in the extraction solvent, the temperature and time of the annealing treatment, etc. can be used for control.
[0071] (Polyolefin)
[0072] In the present disclosure, as the polyolefin constituting the polyolefin microporous membrane, a homopolymer or copolymer such as polyethylene, polypropylene, polybutene, polymethylpentene, or a mixture of two or more thereof can be used. Polyethylene is preferred. As polyethylene, a mixture of high-density polyethylene, high-density polyethylene and ultra-high molecular weight polyethylene, etc. are preferred. In addition, polyethylene and components other than polyethylene can be used in combination. As components other than polyethylene, for example, polypropylene, polybutene, polymethylpentene, copolymers of polypropylene and polyethylene, etc. can be cited. In addition, as polyolefin, polyolefins with different properties can be used in combination with each other. Specifically, polyolefins with different polymerization degrees or branching degrees and lacking compatibility can be used in combination with each other. In other words, polyolefins with different crystallinity, stretchability or molecular orientation can be used in combination with each other.
[0073] In particular, as the polyolefin used in the present disclosure, a polyethylene composition obtained by mixing a high molecular weight polyethylene having a weight average molecular weight of 3 million to 6 million and a low molecular weight polyethylene having a weight average molecular weight of 200,000 to 800,000 is preferably used. This has the following effects: by mixing two or more polyethylenes in appropriate amounts, a network structure accompanying fibrillation during stretching is formed, thereby increasing the void generation rate.
[0074] In particular, the blending ratio of the high molecular weight polyethylene to the low molecular weight polyethylene is preferably 15:85 to 85:15, and more preferably 19:81 to 81:19 in terms of mass ratio.
[0075] As low molecular weight polyethylene, preferably the density is 0.92 g / cm 3 ~0.98g / cm 3 of high-density polyethylene.
[0076] It should be noted that the weight average molecular weight can be obtained by heating and dissolving a sample of the polyolefin microporous membrane in o-dichlorobenzene, and measuring it by GPC (Alliance GPC 2000 manufactured by Waters, chromatographic columns: GMH6-HT and GMH6-HTL) at a column temperature of 135° C. and a flow rate of 1.0 mL / min. Monodisperse polystyrene (manufactured by Tosoh Corporation) can be used for molecular weight calibration.
[0077] In the present disclosure, the calcium content of the polyolefin constituting the polyolefin microporous membrane is preferably 0 ppb or more, more preferably 50 ppb or more, and further preferably 100 ppb or more. In addition, the calcium content of the polyolefin constituting the polyolefin microporous membrane is preferably 1000 ppb or less, more preferably 500 ppb or less, and further preferably 300 ppb or less.
[0078] As a method for adjusting the calcium content to 1000 ppb or less, there is a method of adjusting the amount of metal soap (calcium stearate, etc.) added to the polyolefin after polymerization. Another method is to acid-wash a commercially available polyolefin raw material.
[0079] In the present disclosure, the calcium content in the polyolefin refers to the value determined by the method described in the Example column.
[0080] <Liquid filter>
[0081] The liquid filter substrate of the present disclosure can be processed into a cylindrical object after being appropriately processed to impart affinity with chemical liquids, and used as a liquid filter. The liquid filter is an apparatus for removing particles from a treated liquid that contains particles formed by at least one of organic and inorganic substances, or that may contain the particles. The particles exist in the treated liquid in a solid or gel state. The liquid filter of the present disclosure is suitable for removing very fine particles with a particle size of about several nanometers. In addition, the liquid filter can be used not only in the manufacturing process of semiconductors, but also in other manufacturing processes such as display manufacturing and grinding.
[0082] As substrates for liquid filters, porous substrates such as polytetrafluoroethylene are widely known. When the substrate containing a polyolefin microporous membrane of the above-mentioned present disclosure is used as a substrate for a liquid filter, it has better affinity with chemical liquids than a porous substrate of polytetrafluoroethylene. Therefore, for example, the following effects are exhibited: it is easy to process the filter to impart affinity with chemical liquids; when the filter cartridge is loaded into the filter housing and the chemical liquid is filled into the filter at the beginning of the filtration of the chemical liquid, it is not easy to generate bubbles in the filter cartridge, and the filtration efficiency of the chemical liquid becomes good; and so on. In addition, since the structure of polyethylene itself does not contain halogen elements, it is easy to dispose of the used filter cartridge, which has the effect of reducing the environmental load.
[0083] <Method for producing polyolefin microporous membrane and method for controlling pore structure>
[0084] The polyolefin microporous membrane included in the liquid filter substrate of the present disclosure can be suitably manufactured by the method shown below. That is, it can be suitably manufactured by sequentially carrying out the following steps:
[0085] Step (I), preparing a solution comprising a polyolefin composition and a solvent;
[0086] Step (II), melt-kneading the prepared solution, extruding the obtained melt-kneaded product from a die, cooling and solidifying it to obtain a gel-like molded product;
[0087] Step (III), extruding a portion of the solvent from the gel-like molded product in advance;
[0088] Step (IV) of stretching the gel-like molded product from which a portion of the solvent has been squeezed out in at least one direction;
[0089] In step (V), the solvent is extracted from the interior of the stretched intermediate molded product and the product is washed.
[0090] In step (I), a solution comprising a polyolefin composition and a solvent is prepared. The solvent is preferably a volatile solvent having a boiling point of less than 210°C at least at atmospheric pressure. The solution is preferably a thermoreversible sol-gel solution. In step (I), specifically, the polyolefin composition is heated and dissolved in a solvent, thereby making it sol-gel, and preparing a thermoreversible sol-gel solution. There is no particular limitation on the volatile solvent having a boiling point of less than 210°C at atmospheric pressure, as long as it can swell or dissolve the polyolefin. For example, liquid solvents such as tetralin, ethylene glycol, decalin, toluene, xylene, diethyltriamine, ethylenediamine, dimethyl sulfoxide, and hexane are preferably mentioned. These can be used alone or in combination of two or more. Among them, decalin or xylene is preferred. In addition, in the preparation of the solution, in addition to the above-mentioned volatile solvent having a boiling point of less than 210°C under atmospheric pressure, a non-volatile solvent having a boiling point of 210°C or higher, such as liquid paraffin, paraffin oil, mineral oil, and castor oil, may be included.
[0091] In the solution of step (I), from the viewpoint of controlling the liquid permeability of the polyolefin microporous membrane and the removal performance as a filter material, the concentration of the polyolefin composition is preferably 15% by mass to 40% by mass, and more preferably 20% by mass to 30% by mass. When the concentration of the polyolefin composition is 15% by mass or more, there is a tendency that the mechanical strength does not become too low, so the operability is well maintained, and in addition, there is a tendency to suppress the frequency of occurrence of fractures during the manufacture of the polyolefin microporous membrane. In addition, if the concentration of the polyolefin composition is 40% by mass or less, there is a tendency to easily form pores.
[0092] In step (II), the solution prepared in step (I) is melt-kneaded, the obtained melt-kneaded product is extruded from a die, and cooled and solidified to obtain a gel-like molded product. Preferably, the extrudate is obtained by extruding from a die at a temperature range of from the melting point of the polyolefin composition to a temperature 65°C higher than the melting point, and then the extrudate is cooled to obtain a gel-like molded product. The molded product is preferably shaped into a sheet.
[0093] The method for cooling the extrudate is not particularly limited, and may be a method based on quenching in water or an organic solvent, or a method based on casting on a cooled metal roll. A method based on quenching in water or a volatile solvent used in the preparation of a sol-gel solution is generally adopted. The cooling temperature is preferably 10°C to 40°C. It should be noted that, preferably, a water flow is provided on the surface of the water bath, so that a gel-like sheet can be produced in a state where the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface does not re-attach to the sheet.
[0094] Step (III) is a step of pre-pressing a portion of the solvent in the gel-like molded product before stretching the gel-like molded product in at least one direction. In the step (III), for example, pressure is applied to the surface of the gel-like molded product by passing the gel-like molded product through the gap between two upper and lower conveyor belts or two rollers, so that it can be properly implemented. The amount of the solvent squeezed out needs to be adjusted according to the liquid permeability required by the polyolefin microporous membrane and the removal performance of the filtered object. Specifically, the amount of squeezed solvent can be adjusted to an appropriate range by the extrusion pressure between the upper and lower conveyor belts or rollers, the temperature of the squeezing process, and the number of squeezing times. It should be noted that, for the pressure on the gel-like molded product, it is preferably set in the range of 0.01MPa to 0.5MPa using a roller, etc. More preferably, it is in the range of 0.05MPa to 0.2MPa. The squeezing temperature is preferably 40°C to 100°C. In addition, for the number of squeezing times, it depends on the allowable space of the equipment, so it can be set without special restrictions. It should be noted that, as required, one or more stages of preheating may be performed before squeezing the solvent to remove a portion of the volatile solvent from the sheet. In this case, the preheating temperature is preferably 50° C. to 100° C. In addition, when the preheating is performed, the time is preferably 5 minutes to 9 minutes per stage. In this case, the amount of the volatile solvent to be removed is adjusted by the conveying distance and conveying speed of the heating device.
[0095] Step (IV) is a step of stretching the gel-like molded product in at least one direction. The stretching in step (IV) is preferably biaxial stretching, and any of the methods of sequential biaxial stretching (longitudinal stretching and transverse stretching are performed separately) and simultaneous biaxial stretching (longitudinal stretching and transverse stretching are performed simultaneously) can be appropriately used. In addition, the following methods are also preferred: a method of stretching in the longitudinal direction for multiple times and then stretching in the transverse direction; a method of stretching in the longitudinal direction and stretching in the transverse direction for multiple times; a method of performing sequential biaxial stretching and then further stretching in the longitudinal direction and / or transverse direction once or more times.
[0096] From the viewpoint of controlling the liquid permeability of the polyolefin microporous membrane and the removal performance of the filtered object, the stretching ratio (the product of the longitudinal stretching ratio and the transverse stretching ratio) is preferably 40 to 105 times, and more preferably 50 to 100 times. If the stretching ratio is 40 times or more, there is a tendency to easily suppress the occurrence of uneven thickness of the polyolefin microporous membrane. When the stretching ratio is 105 times or less, there is a tendency to reduce the frequency of fracture in the film formation of the polyolefin microporous membrane. It is preferred to stretch in a state where the solvent remains in a suitable state. The stretching temperature is preferably 80°C to 125°C. Particularly preferably, 100°C to 120°C.
[0097] In addition, a heat setting treatment may be performed after the stretching step (IV).
[0098] From the viewpoint of controlling the liquid permeability of the polyolefin microporous membrane and the removal performance of the filtration object, the heat setting temperature is preferably 100° C. to 143° C. More preferably, it is 105° C. to 138° C. When the heat setting temperature is 100° C. or higher, the liquid permeability of the polyolefin microporous membrane tends to be further improved. When the heat setting temperature is 143° C. or lower, the removal performance of the filtration object of the polyolefin microporous membrane tends to be further improved.
[0099] Step (V) is a step of washing the stretched intermediate molding in order to extract the solvent from the inside of the stretched intermediate molding. Here, for step (V), in order to extract the solvent from the inside of the stretched intermediate molding (stretched film), it is preferably washed with halogenated hydrocarbons such as dichloromethane, hydrocarbon solvents such as hexane, etc. . When the intermediate molding is immersed in a tank containing a solvent for washing, a polyolefin microporous membrane with less eluted components can be obtained after 20 seconds to 150 seconds, so it is preferred, more preferably 25 seconds to 150 seconds, and particularly preferably 30 seconds to 120 seconds. In addition, in order to further improve the effect of washing, it is preferred that the tank is divided into several sections, and the washing solvent is injected from the downstream side of the conveying process of the polyolefin microporous membrane, so that the washing solvent flows toward the upstream side of the conveying process, so that the purity of the washing solvent in the downstream tank is higher than that of the upstream tank. When the tank containing the solvent is divided into several sections, it can be 2 tanks or more than 3 tanks. From the viewpoint of making the purity gradient of the washing solvent in each tank more gentle, the number of tanks storing the solvent is preferably three or more.
[0100] In addition, depending on the performance required of the polyolefin microporous membrane, heat setting can also be performed by annealing (heat treatment). It should be noted that, from the perspective of transportability during the process, the annealing treatment is preferably carried out at 50°C to 150°C, and more preferably at 60°C to 140°C. From the perspective of suppressing the shrinkage of the polyolefin microporous membrane over time, the annealing treatment is preferably at 100°C to 130°C.
[0101] When performing annealing treatment, it is preferred to suppress shrinkage in the width direction of the polyolefin microporous membrane. By suppressing shrinkage in the width direction, there is a tendency for the coefficient of variation of the water flow rate of the polyolefin microporous membrane to become smaller. For example, by performing annealing treatment in a state where both ends of the polyolefin microporous membrane in the width direction are fixed with a clamp or the like, there is a tendency for the polyolefin microporous membrane to suppress shrinkage in the width direction.
[0102] In addition, the pore size, membrane thickness, porosity and water flow rate of the polyolefin microporous membrane can be set within a specified range by appropriately adjusting the formulation of polyolefin, the concentration of the polyolefin composition in the polyolefin solution, the method for preparing the base tape, the method for removing the solvent in the polyolefin solution, the stretching conditions of the base tape, and the heat treatment conditions.
[0103] Example
[0104] Hereinafter, examples, comparative examples, and various measurement methods of the present disclosure will be described, but the present disclosure is not limited to these examples at all.
[0105] [Measurement method]
[0106] (film thickness)
[0107] The film thickness of the polyolefin microporous film was measured using a contact-type film thickness meter (manufactured by Mitutoyo Co., Ltd.). Here, a cylindrical contact terminal having a bottom diameter of 0.5 cm was used as the contact terminal. The measurement pressure was set to 0.1N.
[0108] -average value-
[0109] The film thickness is measured at 11 locations, including the center of the product width and 5 locations at intervals of 26 mm from the center toward each end face, along the width direction (TD direction) of the polyolefin microporous membrane as described above, and the value calculated as the arithmetic mean of the film thickness at each measured location is taken as the average film thickness.
[0110] - Coefficient of variation -
[0111] Along the width direction (TD direction) of the polyolefin microporous membrane, the film thickness of 11 locations, 5 locations at intervals of 26 mm from the center to each end face, was measured as described above, and the standard deviation σTD1 was calculated based on the film thickness value at each measurement location. Next, σTD1 was divided by the average value of the film thickness at a total of 11 locations to calculate the coefficient of variation CVTD1. The same operation was further repeated 9 times at intervals of 50 mm along the length direction of the polyolefin microporous membrane, and the coefficients of variation CVTD1 to CVTD10 were calculated for a total of 10 times. The arithmetic mean of the obtained coefficients of variation CVTD1 to CVTD10 was taken as the coefficient of variation of the film thickness.
[0112] (Porosity)
[0113] The porosity (ε) of the polyolefin microporous membrane was calculated by the following formula.
[0114] ε(%)={1-Ws / (ds·t)}×100
[0115] Ws: Weight per unit area of polyolefin microporous membrane (g / m 2 )
[0116] ds: true density of polyolefin (g / cm 3 )
[0117] t: Thickness of polyolefin microporous membrane (μm)
[0118] In addition, the weight per unit area of the polyolefin microporous membrane was obtained by cutting a sample into 2 cm×2 cm, measuring the mass, and dividing the mass by the area.
[0119] -average value-
[0120] A 2 cm × 2 cm sample was cut out from 7 locations along the width direction (TD direction) of the polyolefin microporous membrane, at the center of the product width and at 3 locations each at 20 mm intervals from the center toward each end surface, and the porosity of the sample was measured as described above. The value calculated as the arithmetic mean of each measured sample was taken as the average porosity.
[0121] - Coefficient of variation -
[0122] Along the width direction (TD direction) of the polyolefin microporous membrane, the porosity of the center of the product width and 3 locations at intervals of 20 mm from the center toward each end surface, a total of 7 locations, was measured as described above, and the standard deviation σTD1 was calculated based on the porosity value at each measured location. Next, σTD1 was divided by the average value of the porosity at a total of 7 locations to calculate the coefficient of variation CVTD1. The same operation was further repeated 9 times at intervals of 50 mm along the length direction of the polyolefin microporous membrane, and the coefficients of variation CVTD1 to CVTD10 were calculated for a total of 10 times. The arithmetic mean of the obtained coefficients of variation CVTD1 to CVTD10 was taken as the coefficient of variation of the porosity.
[0123] (Aperture)
[0124] The mean flow pore size measured by the following method was defined as the pore size of the polyolefin microporous membrane.
[0125] The average flow pore size of the polyolefin microporous membrane based on gas phase / liquid phase replacement is measured by using the pore size distribution measuring instrument (perm-porometer) of PMI company, the porous material automatic pore size distribution measuring system [Capillary Flow Porometer], and the pore size distribution measuring test method [semi-dry method (ASTM E1294-89)]. It should be noted that the test liquid used is a fluorine-based inactive liquid (trade name: Fluorinert) (surface tension value: 16.0 dyne / cm), the measuring temperature is 25°C, the measuring pressure is in the range of 0psi to 500psi, and the measurement is carried out under the following conditions.
[0126] Bubble point parameters: BUBLFLOW = 50, F / PT = 100, MINBPPRES = 0, ZEROTIME = 1, PULSEDELAY = 2
[0127] Wet parameters: V2INCR = 15, PREGINC = 0.9, MINEQTIME = 30, PRESSLEW = 30, FLOWSLEW = 30, EQITER = 50, AVEITER = 10, MAXPDIF = 1, MAXFDIF = 30
[0128] Dry parameters: V2INCR = 40, PREGINC = 2.4, MINEQTIME = 30, PRESSLEW = 30, FLOWSLEW = 30, EQITER = 40, AVEITER = 10, MAXPDIF = 1, MAXFDIF = 30
[0129] -average value-
[0130] Along the width direction (TD direction) of the polyolefin microporous membrane, the pore diameters of five locations, including the center of the product width and two locations at intervals of 50 mm from the center toward each end surface, are measured as described above, and the value calculated as the arithmetic mean of the pore diameters at each measured location is taken as the average pore diameter.
[0131] - Coefficient of variation -
[0132] Along the width direction (TD direction) of the polyolefin microporous membrane, the pore diameters of the center of the product width and 5 locations, 2 locations each at intervals of 50 mm from the center toward each end face, were measured as described above, and the standard deviation σTD1 was calculated based on the pore diameter values at each measurement location. Next, σTD1 was divided by the average value of the pore diameters at a total of 5 locations to calculate the coefficient of variation CVTD1. The same operation was further repeated 9 times at intervals of 50 mm along the length direction of the polyolefin microporous membrane, and the coefficients of variation CVTD1 to CVTD10 were calculated for a total of 10 times. The arithmetic mean of the obtained coefficients of variation CVTD1 to CVTD10 was taken as the coefficient of variation of the pore diameter.
[0133] (Water flow)
[0134] The polyolefin microporous membrane was immersed in ethanol and dried at room temperature (24°C). The polyolefin microporous membrane was cut into 40 mm squares and placed in a stainless steel permeable cell with a diameter of 37 mm (permeable area S: 10.75 cm 2). After the polyolefin microporous membrane on the permeation pool was moistened with a small amount (0.5 ml) of ethanol, a pre-measured amount of pure water V (100 ml) was passed through it under a pressure difference of 90 kPa, and the time Tl (min) required for the entire amount of pure water to pass through was measured. Based on the amount of pure water and the time required for pure water to pass through, the following formula was used to calculate the per unit time (min)·unit area (ft2) under a pressure difference of 1 psi: 2 ) water permeability Vs(L / min / ft 2 The measurement was performed at room temperature (24°C).
[0135] Vs=(V / 1000) / Tl / (S / 929.03) / (90 / 6.895)
[0136] -average value-
[0137] A 40 mm square sample was cut out from 5 locations along the width direction (TD direction) of the polyolefin microporous membrane, including the center of the product width and 2 locations each spaced 15 mm from the center toward each end surface, and the water flow rate was measured as described above for the sample. The value calculated as the arithmetic mean of each measured sample was taken as the average value of the water flow rate.
[0138] - Coefficient of variation -
[0139] Along the width direction (TD direction) of the polyolefin microporous membrane, the water flow rate is measured at the center of the product width and at 2 locations each at intervals of 15 mm from the center toward each end face as described above, and the standard deviation σVs1 is calculated based on the value of the water flow rate at each measurement location. Next, σVs1 is divided by the average value of the water flow rate at a total of 5 locations to calculate the coefficient of variation CVVs1. The same operation is further repeated 9 times at intervals of 50 mm along the length direction of the polyolefin microporous membrane, and the coefficients of variation CVVs1 to CVVs10 are calculated for a total of 10 times. The arithmetic mean of the obtained coefficients of variation CVVs1 to CVVs10 is taken as the coefficient of variation of the water flow rate.
[0140] (Deviation of filtering time)
[0141] As a test liquid as a filtration fluid, an aqueous solution containing a metal colloid (gold colloid) having an average particle size of 5 nm manufactured by Funakoshi Co., Ltd. at a particle concentration of 40 ppb was prepared and used.
[0142] To evaluate the filtration life, 5 cm square polyolefin microporous membranes were cut from three locations along the TD direction of the polyolefin microporous membrane: the center and both end surfaces of the product width. The cut polyolefin microporous membranes were placed in a stainless steel permeable pool with a diameter of 37 mm (permeable area S: 10.75 cm 2). After wetting the polyolefin microporous membrane on the permeable pool with a small amount (0.5 ml) of ethanol, 200 ml of the test liquid was filtered under a pressure difference of 0.1 MPa, and the time TF required for the entire amount of the test liquid to pass was measured. When the value of the shortest filtration time TF is set to 1, the case where the ratio of the value of the longest filtration time to it is 1.2 or less is evaluated as A, and the case where it exceeds 1.3 is evaluated as B.
[0143] (Capture performance)
[0144] The particle capture rate is calculated using the following formula based on the metal colloid concentration (M1) of the test solution before the filtration time is measured and the metal colloid concentration (M2) of the filtrate after passing through the polyolefin microporous membrane used in the filtration time measurement. Along the TD direction of the polyolefin microporous membrane, the arithmetic mean of the capture rates measured at the center and both end faces of the product width is calculated as the capture rate of the polyolefin microporous membrane. As for the metal concentration of the solution, the ICP-OES method (high-frequency inductively coupled plasma emission spectrometry, device name: Agilent-ICP-OES-5100, Agilent Technologies Co., Ltd.) is used to dilute the standard reagent and use a standard curve obtained by taking 5 or more points in the concentration range of 0 ppb to 100 ppb to determine the metal concentration. The capture performance is evaluated according to the following criteria.
[0145] Capture rate (%) = ((M1-M2) / (M1)) × 100
[0146] -Evaluation Criteria-
[0147] A: When the capture rate is 80% or more
[0148] B: When the collection rate is 60% or more and less than 80%
[0149] C: When the collection rate is 30% or more and less than 60%
[0150] (Calcium (Ca) content)
[0151] 0.1 g of a measurement sample is accurately weighed in a fluororesin container, ultra-high purity nitric acid is added and microwave decomposition is performed, and the calcium content is quantified at the ppb level by ICP (inductively coupled plasma) mass spectrometry (ICP-MS apparatus name: Agilent 7500cs, Agilent Technologies, Inc.).
[0152] (Calcium (Ca) elution amount from porous membrane)
[0153] The polyolefin microporous membrane sample with surface dirt removed was placed at 4000 cm 2Place in a fluororesin container and inject 200g of 10% by mass hydrochloric acid extract containing 60% by mass isopropanol. After the sample is immersed in the container for 24 hours, the Ca concentration in the liquid is quantified to 0.1ppb using the ICP-OES method (high-frequency inductively coupled plasma emission spectrometry, device name: Agilent-ICP-OES-5100, Agilent Technologies Co., Ltd.). The Ca dissolution amount from the polyolefin microporous membrane is calculated based on the mass of the extract, the surface area of the polyolefin microporous membrane, and the Ca concentration in the extract, expressed as μg / m 2 Find the unit of .
[0154] (Method for producing polyolefin microporous membrane)
[0155] Hereinafter, the details of the method for producing the polyolefin microporous membrane in each of Examples and Comparative Examples will be described.
[0156] The main differences in the preparation methods between the embodiment and the comparative example are: in the embodiment, the dichloromethane bath is set to 3 slots, on the other hand, in the comparative example, it is set to 2 slots; and, when performing the heat treatment, in the embodiment, the width is fixed to be constant in the TD direction, on the other hand, in the comparative example, the width is not fixed.
[0157] <Example 1>
[0158] A polyethylene composition was used in which the following substances were mixed: 22 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 140 ppb; and 5 parts by mass of high-density polyethylene having a weight average molecular weight of 500,000 and a Ca content of 230 ppb. A mixed solvent of 72 parts by mass of liquid paraffin and 1 part by mass of decalin (decalin) prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 27% by mass, thereby preparing a polyethylene solution.
[0159] The polyethylene solution was extruded from a die in a sheet form at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a gel-like sheet (base tape) was prepared while setting a water flow on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 5 times (longitudinal stretching), then stretched in the width direction at a temperature of 112°C and a ratio of 15 times (transverse stretching), and then heat-treated at a temperature of 115°C (heat setting).
[0160] Next, the heat-treated base tape is immersed in a dichloromethane bath divided into three grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the starting groove and the third groove is used as the ending groove, the purity of the cleaning solvent is (low) the first groove < the second groove < the third groove (high). Then, the dichloromethane is dried and removed at 40°C, the width is fixed to a constant in the TD direction, and the heat treatment in the TD direction is performed at 110°C for 1 minute, and cooled at 60°C for 20 seconds, thereby obtaining a substrate for a liquid filter formed by a polyolefin microporous membrane.
[0161] The physical properties of the obtained liquid filter substrate are shown in Table 1. In addition, the physical properties of the following Examples and Comparative Examples are also shown in Table 1 or Table 2.
[0162] <Example 2>
[0163] A liquid filter substrate composed of a polyolefin microporous membrane was obtained in the same manner as in Example 1 except that the longitudinal stretching ratio was set to 6 times.
[0164] <Example 3>
[0165] A liquid filter substrate composed of a polyolefin microporous membrane was obtained in the same manner as in Example 1 except that the longitudinal stretching ratio was 6.5 times and the transverse stretching ratio was 13.8 times.
[0166] <Example 4>
[0167] A polyethylene composition was used in which 21 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 110 ppb and 5 parts by mass of high density polyethylene having a weight average molecular weight of 500,000 and a Ca content of 230 ppb were mixed. A mixed solvent of 73 parts by mass of liquid paraffin and 1 part by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 26% by mass to prepare a polyethylene solution.
[0168] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of the liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 5 times (longitudinal stretching), then stretched in the width direction at a temperature of 115°C and a ratio of 15 times (transverse stretching), and then heat-treated at a temperature of 125°C (heat setting).
[0169] Next, the heat-treated base tape is immersed in a dichloromethane bath divided into three grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the starting groove and the third groove is used as the ending groove, the purity of the cleaning solvent is (low) the first groove < the second groove < the third groove (high). Then, the dichloromethane is dried and removed at 40°C, the width is fixed to a constant in the TD direction, and the heat treatment in the TD direction is performed at 120°C for 1 minute, and cooled at 60°C for 20 seconds, thereby obtaining a substrate for a liquid filter formed by a polyolefin microporous membrane.
[0170] <Example 5>
[0171] A polyethylene composition was used in which 18 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 140 ppb and 5 parts by mass of high density polyethylene having a weight average molecular weight of 500,000 and a Ca content of 230 ppb were mixed. A mixed solvent of 76 parts by mass of liquid paraffin and 1 part by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 23% by mass to prepare a polyethylene solution.
[0172] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 4 times (longitudinal stretching), then stretched in the width direction at a temperature of 115°C and a ratio of 15 times (transverse stretching), and then heat-treated at a temperature of 125°C (heat setting).
[0173] Next, the heat-treated base tape is immersed in a dichloromethane bath divided into three grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the starting groove and the third groove is used as the ending groove, the purity of the cleaning solvent is (low) the first groove < the second groove < the third groove (high). Then, the dichloromethane is dried and removed at 40°C, the width is fixed to a constant in the TD direction, and the heat treatment in the TD direction is performed at 120°C for 1 minute, and cooled at 60°C for 20 seconds, thereby obtaining a substrate for a liquid filter formed by a polyolefin microporous membrane.
[0174] <Example 6>
[0175] A polyethylene composition was used in which 3 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.2 million and a Ca content of 31 ppm and 14 parts by mass of high density polyethylene having a weight average molecular weight of 400,000 and a Ca content of 34 ppm were mixed. A mixed solvent of 51 parts by mass of liquid paraffin and 32 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 17% by mass, thereby preparing a polyethylene solution.
[0176] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C at a ratio of 4.5 times (longitudinal stretching), and then stretched in the width direction at a temperature of 115°C at a ratio of 8 times (transverse stretching), and then heat-treated at a temperature of 125°C (heat setting).
[0177] Next, the heat-treated base tape is immersed in a dichloromethane bath divided into three grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the starting groove and the third groove is used as the ending groove, the purity of the cleaning solvent is (low) the first groove < the second groove < the third groove (high). Then, the dichloromethane is dried and removed at 40°C, the width is fixed to a constant in the TD direction, and the heat treatment in the TD direction is performed at 120°C for 1 minute, and cooled at 60°C for 20 seconds, thereby obtaining a substrate for a liquid filter formed by a polyolefin microporous membrane.
[0178] <Example 7>
[0179] A polyethylene composition was used in which 12 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.2 million and a Ca content of 31 ppm and 5 parts by mass of high density polyethylene having a weight average molecular weight of 400,000 and a Ca content of 34 ppm were mixed. A mixed solvent of 51 parts by mass of liquid paraffin and 32 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 17% by mass, thereby preparing a polyethylene solution.
[0180] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of the liquid paraffin from the base tape. Then, the base tape was stretched at a temperature of 100°C and a ratio of 4 times in the longitudinal direction (longitudinal stretching), and then stretched at a temperature of 115°C and a ratio of 9 times in the width direction (transverse stretching), and then heat-treated at a temperature of 125°C (heat setting).
[0181] Next, the heat-treated base tape is immersed in a dichloromethane bath divided into three grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the starting groove and the third groove is used as the ending groove, the purity of the cleaning solvent is (low) the first groove < the second groove < the third groove (high). Then, the dichloromethane is dried and removed at 40°C, the width is fixed to a constant in the TD direction, and the heat treatment in the TD direction is performed at 120°C for 1 minute, and cooled at 60°C for 20 seconds, thereby obtaining a substrate for a liquid filter formed by a polyolefin microporous membrane.
[0182] <Example 8>
[0183] A polyethylene composition was used in which 6 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.2 million and a Ca content of 31 ppm and 24 parts by mass of high density polyethylene having a weight average molecular weight of 400,000 and a Ca content of 34 ppm were mixed. A mixed solvent of 68 parts by mass of liquid paraffin and 2 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 30 parts by mass to prepare a polyethylene solution.
[0184] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 95°C and a ratio of 4 times (longitudinal stretching), and then stretched in the width direction at a temperature of 110°C and a ratio of 11 times (transverse stretching), and then heat-treated at a temperature of 120°C (heat setting).
[0185] Next, the heat-treated base tape is immersed in a dichloromethane bath divided into three grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the starting groove and the third groove is used as the ending groove, the purity of the cleaning solvent is (low) the first groove < the second groove < the third groove (high). Then, the dichloromethane is dried and removed at 40°C, the width is fixed to a constant in the TD direction, and the heat treatment in the TD direction is performed at 120°C for 1 minute, and cooled at 60°C for 20 seconds, thereby obtaining a substrate for a liquid filter formed by a polyolefin microporous membrane.
[0186] <Example 9>
[0187] A polyethylene composition was used in which 15 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.2 million and a Ca content of 31 ppm and 15 parts by mass of high density polyethylene having a weight average molecular weight of 400,000 and a Ca content of 34 ppm were mixed. A mixed solvent of 68 parts by mass of liquid paraffin and 2 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 30 parts by mass to prepare a polyethylene solution.
[0188] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 4 times (longitudinal stretching), and then stretched in the width direction at a temperature of 115°C and a ratio of 10 times (transverse stretching), and then heat-treated at a temperature of 125°C (heat setting).
[0189] Next, the heat-treated base tape is immersed in a dichloromethane bath divided into three grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the starting groove and the third groove is used as the ending groove, the purity of the cleaning solvent is (low) the first groove < the second groove < the third groove (high). Then, the dichloromethane is dried and removed at 40°C, the width is fixed to a constant in the TD direction, and the heat treatment in the TD direction is performed at 120°C for 1 minute, and cooled at 60°C for 20 seconds, thereby obtaining a substrate for a liquid filter formed by a polyolefin microporous membrane.
[0190] <Example 10>
[0191] A polyethylene composition was used in which 17 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.2 million and a Ca content of 31 ppm and 4 parts by mass of high density polyethylene having a weight average molecular weight of 400,000 and a Ca content of 34 ppm were mixed. A mixed solvent of 78 parts by mass of liquid paraffin and 1 part by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 21% by mass, thereby preparing a polyethylene solution.
[0192] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of the liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 4 times (longitudinal stretching), and then stretched in the width direction at a temperature of 115°C and a ratio of 8 times (transverse stretching), and then heat-treated at a temperature of 125°C (heat setting).
[0193] Next, the heat-treated base tape is immersed in a dichloromethane bath divided into three grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the starting groove and the third groove is used as the ending groove, the purity of the cleaning solvent is (low) the first groove < the second groove < the third groove (high). Then, the dichloromethane is dried and removed at 40°C, the width is fixed to a constant in the TD direction, and the heat treatment in the TD direction is performed at 120°C for 1 minute, and cooled at 60°C for 20 seconds, thereby obtaining a substrate for a liquid filter formed by a polyolefin microporous membrane.
[0194] <Comparative Example 1>
[0195] A polyethylene composition was used in which 22 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 140 ppb and 5 parts by mass of high density polyethylene having a weight average molecular weight of 500,000 and a Ca content of 230 ppb were mixed. A mixed solvent of 72 parts by mass of liquid paraffin and 1 part by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 27 parts by mass to prepare a polyethylene solution.
[0196] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of the liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 8 times (longitudinal stretching), and then stretched in the width direction at a temperature of 112°C and a ratio of 10 times (transverse stretching), and then heat-treated at a temperature of 115°C (heat setting).
[0197] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the end dipping side is used as the second tank, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and the base tape is heated to 110°C while being transported on a roller, thereby obtaining a substrate for a liquid filter formed of a polyolefin microporous membrane.
[0198] <Comparative Example 2>
[0199] A liquid filter substrate composed of a polyolefin microporous membrane was prepared in the same manner as in Comparative Example 1 except that the longitudinal stretching ratio was set to 9 times.
[0200] <Comparative Example 3>
[0201] A liquid filter substrate composed of a polyolefin microporous membrane was prepared in the same manner as in Comparative Example 1 except that the longitudinal stretching ratio was 10 times and the transverse stretching ratio was 8 times.
[0202] <Comparative Example 4>
[0203] A polyethylene composition was used in which 3 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.2 million and a Ca content of 31 ppm and 14 parts by mass of high density polyethylene having a weight average molecular weight of 400,000 and a Ca content of 34 ppm were mixed. A mixed solvent of 51 parts by mass of liquid paraffin and 32 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 17% by mass, thereby preparing a polyethylene solution.
[0204] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 190°C, and then the extrudate was cooled in a water bath at 20°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of the liquid paraffin from the base tape. Then, the base tape was stretched at a temperature of 100°C and a ratio of 6 times in the longitudinal direction (longitudinal stretching), and then stretched at a temperature of 115°C and a ratio of 6 times in the width direction (transverse stretching), and then heat-treated at a temperature of 125°C (heat setting).
[0205] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0206] <Comparative Example 5>
[0207] A polyethylene composition was used in which 5 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 23 parts by mass of high density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed. A mixed solvent of 69 parts by mass of liquid paraffin and 3 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 28% by mass to prepare a polyethylene solution.
[0208] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 160°C, and then the extrudate was cooled in a water bath at 25°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet. The base tape was dried at 55°C for 10 minutes and then at 95°C for 10 minutes to remove decalin from the base tape, and then the base tape was conveyed while applying a pressure of 20 kgf / m (1.96 MPa) on a roller heated to 85°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 5.8 times (longitudinal stretching), then stretched in the width direction at a temperature of 100°C and a ratio of 14 times (transverse stretching), and then heat-treated at a temperature of 118°C (heat setting).
[0209] Next, the heat-treated base tape is immersed in two dichloromethane baths divided into two grooves for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first groove is used as the first groove and the second groove is used as the end of the dipping side, the purity of the cleaning solvent is (low) the first groove < the second groove (high). Then, the dichloromethane is dried and removed at 45°C, and the base tape is heated to 110°C while being transported on a roller, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0210] <Comparative Example 6>
[0211] In Comparative Example 5, the base tape is conveyed while applying a pressure of 40 kgf / m (3.92 MPa) to a roller heated to 40°C, and after removing a portion of the liquid paraffin from the base tape, it is stretched in the length direction at a temperature of 90°C and a ratio of 5.8 times (longitudinal stretching), then stretched in the width direction at a temperature of 90°C and a ratio of 14 times (transverse stretching), and then heat treated (heat setting) at a temperature of 124°C. Except for this, the same operation is performed to obtain a substrate for a liquid filter formed of a polyolefin microporous membrane.
[0212] <Comparative Example 7>
[0213] In Comparative Example 5, the base tape is conveyed while applying a pressure of 5 kgf / m (0.49 MPa) to a roller heated to 95°C, and after removing a portion of the liquid paraffin from the base tape, it is stretched in the length direction at a temperature of 95°C and a ratio of 6.5 times (longitudinal stretching), then stretched in the width direction at a temperature of 95°C and a ratio of 13 times (transverse stretching), and then heat treated (heat setting) at a temperature of 114°C. Except for this, the same operation is performed to obtain a substrate for a liquid filter formed of a polyolefin microporous membrane.
[0214] <Comparative Example 8>
[0215] In Comparative Example 5, a polyethylene composition in which 4 parts by mass of an ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 31 parts by mass of a high-density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed was used, and a mixed solvent of 55 parts by mass of liquid paraffin and 10 parts by mass of decalin prepared in advance was mixed with the polyethylene composition in such a manner that the concentration of the total amount of the polyethylene resin became 35% by mass to prepare a polyethylene solution, and the base tape from which a part of the liquid paraffin had been removed was stretched in the length direction at a temperature of 100° C. and a ratio of 5 times (longitudinal stretching), then stretched in the width direction at a temperature of 100° C. and a ratio of 9 times (transverse stretching), and then heat-treated (heat-set) at a temperature of 114° C. was performed in the same manner to obtain a substrate for a liquid filter formed of a polyolefin microporous membrane.
[0216] <Comparative Example 9>
[0217] In Comparative Example 5, a polyethylene composition in which 8 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 24 parts by mass of high-density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm are mixed is used, and a mixed solvent of 53 parts by mass of liquid paraffin and 15 parts by mass of decalin prepared in advance is mixed with the polyethylene composition in such a manner that the concentration of the total amount of the polyethylene resin becomes 32% by mass to prepare a polyethylene solution, and the base tape from which a portion of the liquid paraffin has been removed is stretched in the length direction at a temperature of 100° C. and at a ratio of 4 times (longitudinal stretching), and then stretched in the width direction at a temperature of 100° C. and at a ratio of 15 times (transverse stretching), and the same operation is performed except that the above-mentioned operations are performed to obtain a substrate for a liquid filter formed of a polyolefin microporous membrane.
[0218] <Comparative Example 10>
[0219] A polyethylene composition was used in which 14 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 6 parts by mass of high density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed. A mixed solvent of 55 parts by mass of liquid paraffin and 25 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 20% by mass, thereby preparing a polyethylene solution.
[0220] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 160°C, and then the extrudate was cooled in a water bath at 25°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 55°C for 10 minutes and then at 95°C for 10 minutes to remove decalin from the base tape, and then, the base tape was conveyed while applying a pressure of 20 kgf / m (1.96 MPa) on a roller heated to 85°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 5 times (longitudinal stretching), and then stretched in the width direction at a temperature of 100°C and a ratio of 14 times (transverse stretching), and then heat-treated at a temperature of 128°C (heat setting).
[0221] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 45°C, and heat-treated while being transported on a roller heated to 110°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0222] <Comparative Example 11>
[0223] In Comparative Example 10, a substrate for a liquid filter formed of a polyolefin microporous membrane was obtained by the same operation except that a polyethylene composition was used in which 12 parts by mass of an ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 8 parts by mass of a high-density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed.
[0224] <Comparative Example 12>
[0225] In Comparative Example 10, a liquid filter substrate composed of a polyolefin microporous membrane was obtained in the same manner except that the heat treatment (heat setting) temperature after the biaxial stretching was 134°C.
[0226] <Comparative Example 13>
[0227] In Comparative Example 10, a polyethylene composition containing 20 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 5 parts by mass of high-density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm was mixed, and a mixed solvent of 50 parts by mass of liquid paraffin and 25 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 25% by mass to prepare a polyethylene solution. The polyethylene solution was extruded in the same manner as in Comparative Example 10, and the obtained base tape was heated and dried, and then conveyed on a roller heated to 95° C. while applying a pressure of 10 kgf / m (0.98 MPa) to remove a portion of the liquid paraffin from the base tape. The same operation was performed except that the above-mentioned operation was performed to obtain a substrate for a liquid filter formed of a polyolefin microporous membrane.
[0228] <Comparative Example 14>
[0229] A polyethylene composition was used in which 3 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 12 parts by mass of high density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed. A mixed solvent of 60 parts by mass of liquid paraffin and 25 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 15% by mass, thereby preparing a polyethylene solution.
[0230] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 160°C, and then the extrudate was cooled in a water bath at 25°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 55°C for 10 minutes and then at 95°C for 10 minutes to remove decalin from the base tape, and then, the base tape was conveyed while applying a pressure of 20 kgf / m (1.96 MPa) on a roller heated to 85°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 100°C and a ratio of 6 times (longitudinal stretching), and then stretched in the width direction at a temperature of 100°C and a ratio of 12 times (transverse stretching), and then heat-treated at a temperature of 136°C (heat setting).
[0231] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 45°C, and heat-treated while being transported on a roller heated to 110°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0232] <Comparative Example 15>
[0233] In Comparative Example 14, a polyethylene composition comprising 2 parts by mass of ultra-high molecular weight polyethylene having a weight-average molecular weight of 4.6 million and a Ca content of 30 ppm and 18 parts by mass of high-density polyethylene having a weight-average molecular weight of 560,000 and a Ca content of 36 ppm is used, and a mixed solvent of 55 parts by mass of liquid paraffin and 25 parts by mass of decalin prepared in advance is mixed with the polyethylene composition in such a manner that the concentration of the total amount of the polyethylene resin becomes 20% by mass to prepare a polyethylene solution. Except for this, the same operation is performed to obtain a substrate for a liquid filter formed of a polyolefin microporous membrane.
[0234] <Comparative Example 16>
[0235] In Comparative Example 14, a liquid filter substrate composed of a polyolefin microporous membrane was obtained in the same manner except that the heat treatment (heat setting) temperature after the biaxial stretching was 142°C.
[0236] <Comparative Example 17>
[0237] In Comparative Example 14, a polyethylene composition containing 6.5 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 18.5 parts by mass of high-density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm was mixed, and a mixed solvent of 50 parts by mass of liquid paraffin and 25 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 25% by mass to prepare a polyethylene solution. This polyethylene solution was extruded in the same manner as in Comparative Example 14, and the obtained base tape was heated and dried, and then conveyed on a roller heated to 95° C. while applying a pressure of 10 kgf / m (0.98 MPa) to remove a part of the liquid paraffin from the base tape. The same operation was performed except that the liquid filter substrate composed of a polyolefin microporous membrane was obtained.
[0238] <Comparative Example 18>
[0239] A polyethylene composition was used in which 18.4 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 5.1 million and a Ca content of 140 ppb and 4.6 parts by mass of high density polyethylene having a weight average molecular weight of 650,000 and a Ca content of 270 ppb were mixed. A mixed solvent of 74.5 parts by mass of liquid paraffin and 2.5 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 23% by mass, thereby preparing a polyethylene solution.
[0240] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 155°C, and then the extrudate was cooled in a water bath at 20°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 115°C and a ratio of 5.8 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 130°C (heat setting).
[0241] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0242] <Comparative Example 19>
[0243] A polyethylene composition was used in which 18.4 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 5.1 million and a Ca content of 140 ppb and 4.6 parts by mass of high density polyethylene having a weight average molecular weight of 650,000 and a Ca content of 270 ppb were mixed. A mixed solvent of 75.9 parts by mass of liquid paraffin and 1.1 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 23% by mass, thereby preparing a polyethylene solution.
[0244] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 158°C, and then the extrudate was cooled in a water bath at 18°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 95°C and a ratio of 5.8 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 140°C (heat setting).
[0245] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0246] <Comparative Example 20>
[0247] A polyethylene composition was used in which 12.5 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 5.1 million and a Ca content of 140 ppb and 12.5 parts by mass of high density polyethylene having a weight average molecular weight of 650,000 and a Ca content of 270 ppb were mixed. A mixed solvent of 72.5 parts by mass of liquid paraffin and 2.5 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin was 25% by mass to prepare a polyethylene solution.
[0248] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 156°C, and then the extrudate was cooled in a water bath at 18°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 110°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 115°C and a ratio of 5.8 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 115°C (heat setting).
[0249] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0250] <Comparative Example 21>
[0251] A polyethylene composition was used in which 6 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 5.1 million and a Ca content of 140 ppb was mixed, and 24 parts by mass of high density polyethylene having a weight average molecular weight of 650,000 and a Ca content of 270 ppb was mixed. A mixed solvent of 67.5 parts by mass of liquid paraffin and 2.5 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin was 30 parts by mass to prepare a polyethylene solution.
[0252] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 164°C, and then the extrudate was cooled in a water bath at 16°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 30°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 115°C and a ratio of 5.8 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 140°C (heat setting).
[0253] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 125°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0254] <Comparative Example 22>
[0255] A polyethylene composition was used in which 4.6 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 5.1 million and a Ca content of 140 ppb and 18.4 parts by mass of high density polyethylene having a weight average molecular weight of 650,000 and a Ca content of 270 ppb were mixed. A mixed solvent of 74.5 parts by mass of liquid paraffin and 2.5 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 23% by mass, thereby preparing a polyethylene solution.
[0256] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 164°C, and then the extrudate was cooled in a water bath at 16°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 30°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 115°C and a ratio of 5.8 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 128°C (heat setting).
[0257] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0258] <Comparative Example 23>
[0259] A polyethylene composition was used in which 4.6 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 5.1 million and a Ca content of 140 ppb and 18.4 parts by mass of high density polyethylene having a weight average molecular weight of 650,000 and a Ca content of 270 ppb were mixed. A mixed solvent of 74.5 parts by mass of liquid paraffin and 2.5 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 23% by mass, thereby preparing a polyethylene solution.
[0260] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 164°C, and then the extrudate was cooled in a water bath at 16°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 30°C to remove a portion of the liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 115°C and a ratio of 7 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 11 times (transverse stretching), and then heat-treated at 125°C (heat setting).
[0261] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0262] <Comparative Example 24>
[0263] A polyethylene composition was used in which 10.0 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 5.1 million and a Ca content of 140 ppb and 10.0 parts by mass of high density polyethylene having a weight average molecular weight of 650,000 and a Ca content of 270 ppb were mixed. A mixed solvent of 77.3 parts by mass of liquid paraffin and 2.7 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin was 20% by mass to prepare a polyethylene solution.
[0264] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 156°C, and then the extrudate was cooled in a water bath at 16°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 30°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 115°C and a ratio of 7 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 135°C (heat setting).
[0265] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0266] <Comparative Example 25>
[0267] A polyethylene composition was used in which 24 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 5.1 million and a Ca content of 140 ppb and 6 parts by mass of high density polyethylene having a weight average molecular weight of 650,000 and a Ca content of 270 ppb were mixed. A mixed solvent of 67.7 parts by mass of liquid paraffin and 2.3 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin was 30 parts by mass to prepare a polyethylene solution.
[0268] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 158°C, and then the extrudate was cooled in a water bath at 16°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 30°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 115°C and a ratio of 7 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 9 times (transverse stretching), and then heat-treated at 130°C (heat setting).
[0269] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and the base tape is heat-treated while being transported on a roller heated to 105°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0270] <Comparative Example 26>
[0271] A polyethylene composition was used in which 15 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 15 parts by mass of high density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed. A mixed solvent of 67.5 parts by mass of liquid paraffin and 2.5 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin was 30 parts by mass to prepare a polyethylene solution.
[0272] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 155°C, and then the extrudate was cooled in a water bath at 20°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 90°C and a ratio of 5.9 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 130°C (heat setting).
[0273] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0274] <Comparative Example 27>
[0275] A polyethylene composition was used in which 18 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 5 parts by mass of high density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed. A mixed solvent of 75.9 parts by mass of liquid paraffin and 1.1 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 23% by mass, thereby preparing a polyethylene solution.
[0276] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 158°C, and then the extrudate was cooled in a water bath at 18°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then the base tape was conveyed while applying a pressure of 0.05 MPa on a roller heated to 90°C to remove a portion of the liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 90°C and a ratio of 7.0 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 130°C (heat setting).
[0277] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and the base tape is transported on a roller heated to 100°C while being heat-treated, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0278] <Comparative Example 28>
[0279] A polyethylene composition was used in which 18 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 5 parts by mass of high density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed. A mixed solvent of 75.9 parts by mass of liquid paraffin and 1.1 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 23% by mass, thereby preparing a polyethylene solution.
[0280] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 156°C, and then the extrudate was cooled in a water bath at 18°C, and a base tape was prepared while a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface did not re-adhere to the sheet. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 110°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 105°C and a ratio of 6.5 times (longitudinal stretching), and then stretched in the width direction at a temperature of 115°C and a ratio of 13 times (transverse stretching), and then heat-treated at 130°C (heat setting).
[0281] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and the base tape is transported on a roller heated to 100°C while being heat-treated, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0282] <Comparative Example 29>
[0283] A polyethylene composition was used in which 15 parts by mass of ultra-high molecular weight polyethylene having a weight average molecular weight of 4.6 million and a Ca content of 30 ppm and 15 parts by mass of high density polyethylene having a weight average molecular weight of 560,000 and a Ca content of 36 ppm were mixed. A mixed solvent of 67.5 parts by mass of liquid paraffin and 2.5 parts by mass of decalin prepared in advance was mixed with the polyethylene composition so that the concentration of the total amount of the polyethylene resin became 30% by mass, thereby preparing a polyethylene solution.
[0284] The polyethylene solution was extruded from a die in the form of a sheet at a temperature of 164°C, and then the extrudate was cooled in a water bath at 16°C, and a water flow was set on the surface of the water bath so that the mixed solvent discharged from the gelled sheet in the water bath and suspended on the water surface would not re-adhere to the sheet, thereby preparing a base tape. The base tape was dried at 60°C for 7 minutes and then at 95°C for 7 minutes to remove decalin from the base tape, and then, it was conveyed while applying a pressure of 0.05 MPa on a roller heated to 30°C to remove a portion of liquid paraffin from the base tape. Then, the base tape was stretched in the longitudinal direction at a temperature of 90°C and a ratio of 5.9 times (longitudinal stretching), and then stretched in the width direction at a temperature of 105°C and a ratio of 13 times (transverse stretching), and then heat-treated at 120°C (heat setting).
[0285] Next, the heat-treated base tape is immersed in two dichloromethane baths for 30 seconds each, while extracting liquid paraffin. It should be noted that when the first dipping side is used as the first tank and the second dipping side is used as the end dipping side, the purity of the cleaning solvent is (low) the first tank < the second tank (high). Then, the dichloromethane is dried and removed at 40°C, and heat-treated while being transported on a roller heated to 120°C, thereby obtaining a liquid filter substrate formed of a polyolefin microporous membrane.
[0286] [Table 1]
[0287]
[0288] [Table 2]
[0289]
[0290] The evaluation results shown in Tables 1 and 2 reveal the following.
[0291] It can be seen that the liquid filter substrates formed of the polyolefin microporous membranes of Examples 1 to 10 having a coefficient of variation of water flow of 0.100 or less have better variation in filtration time than the liquid filter substrates formed of the polyolefin microporous membranes of Comparative Examples 1 to 29 having a coefficient of variation of water flow of more than 0.100.
[0292] It can be seen that for the liquid filter substrate formed by the polyolefin microporous membranes of Examples 1 to 5 in which the Ca content contained in the polyethylene used as the raw material is less than 1 ppm, the Ca elution amount is suppressed compared with the liquid filter substrate formed by the polyolefin microporous membranes of Examples 6 to 10 in which the Ca content is greater than 1 ppm.
[0293] It can be seen that the liquid filter substrate formed by the polyolefin microporous membranes of Examples 1 to 5 and 8 to 10 having an average pore size of less than 20 nm has better capture performance than the liquid filter substrate formed by the polyolefin microporous membranes of Examples 6 to 7 having an average pore size of more than 20 nm.
[0294] The entire disclosure of Japanese Patent Application No. 2022-120889 filed on July 28, 2022 is incorporated into this specification by reference.
[0295] All documents, patent applications, and technical standards described in this specification are incorporated into this specification by reference to the same extent as if each document, patent application, and technical standard were specifically and individually described.
Claims
1. A liquid filter substrate, comprising a polyolefin microporous membrane, The average pore size of the polyolefin microporous membrane is 1 nm to 50 nm. The average water flow rate of the polyolefin microporous membrane is 0.003 L / min / ft 2 / psi~0.180L / min / ft 2 / psi, The coefficient of variation of water flow rate of the polyolefin microporous membrane is 0.100 or less.
2. The liquid filter substrate according to claim 1, wherein The coefficient of variation of the pore diameter of the polyolefin microporous membrane is 0.100 or less.
3. The liquid filter substrate according to claim 1, wherein The coefficient of variation of the film thickness of the polyolefin microporous film is 0.100 or less.
4. The liquid filter substrate according to claim 1, wherein The coefficient of variation of the porosity of the polyolefin microporous membrane is 0.100 or less.
5. The liquid filter substrate according to claim 1, wherein The average value of the film thickness of the polyolefin microporous film is 3 μm to 20 μm.
6. The liquid filter substrate according to claim 1, wherein The average porosity of the polyolefin microporous membrane is 35% to 60%.
Citation Information
Patent Citations
Enameled steel plate having excellent sound insulating property
JP1981084951A
Coating steel plate for droneeanddredrone can and droneeanddironing can
JP1981084952A
Rock wool board with uneven pattern and its manufacture
JP1981084953A
Base material for liquid filter
JP2014217800A
Base material for liquid filter
JP2014218563A